Competing cardiovascular outcomes associated with electrocardiographic left ventricular hypertrophy: the Atherosclerosis Risk in Communities study - Desai, Chintan S. (2011)
OBJECTIVE: Individuals with electrocardiographically-determined left ventricular hypertrophy (ECG LVH) are at risk for multiple cardiovascular disease (CVD) outcomes simultaneously. We sought to characterize the competing incidences for subtypes of first CVD events or non-CVD death in those with and without ECG LVH. DESIGN: We included participants in the Atherosclerosis Risk in Communities (ARIC) study. ECG LVH was defined according to Sokolow-Lyon criteria. We used competing Cox models to compare hazards for diverse outcomes within groups (e.g., among those with ECG LVH) and for a given event between groups (ECG LVH versus no ECG LVH). RESULTS: After 15 years, men with ECG LVH at baseline (N = 383) had cumulative incidence of first CVD events and non-CVD deaths of 29.2% and 6.1%, respectively (hazard ratio 4.86; 95% CI, 3.04–7.77). In men without ECG LVH (N = 6576) the incidence of any first CVD event and non-CVD death was 18.9% and 6.9%, respectively (hazard ratio 2.67; 2.39–2.98). Similar associations were observed in women (N = 381 with and N = 8187 without ECG LVH). Coronary heart disease (CHD) was the most common first event in men with ECG LVH (15.0%) and heart failure (HF) was the most common first event in women with ECG LVH (10.5%). After adjustment for risk factors including systolic blood pressure, any CVD event remained the most likely first event. CONCLUSIONS: Among middle-aged individuals with ECG LVH, the most likely first events are CHD in men and HF in women; these results may have implications for preventive approaches.